Goosebumps : The Curse of the Mummy's Tomb - Book 5 - Stine, R. L. (London : Scholastic, 2015)
Gabe is exploring the tunnels of an ancient Egyptian pyramid. Unfortunately, Gabe is also lost! And Gabe is not alone. Someone else is in the pyramid, too. Someone. Or something.
"Goosebumps now a frightful new film!"--Cover.
Keywords: Mummies -- Juvenile fiction; Pyramids -- Juvenile fiction; Mummies -- Fiction; Egypt -- Juvenile fiction